ASSOCIATION OF SELECTED RISK FACTORS OF CORONARY HEART DISEASE WITH LIPID PROFILE - Sahu, Trilochan; Patnaik, Lipilekha; Rao E, Venkata; Ray, Subhashree; Panigrahi, Sandeep Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The objectives of this study is to assess the association of selected risk factors for coronary heart disease (CHD) with lipid profile. Methods: A cross-sectional study was conducted during May 2013â€“April 2014 among 350 subjects of 25â€“64 years selected by systematic random sampling. Data on sociodemographic and medical and personal history along with anthropometric measurements were collected through house-to-house visit. Blood sample was analyzed for fasting blood sugar and lipid profile. Results: In this study, 38.58% belong to the age group of 25â€“35 years and 58% were female. Majority (45.43%) of the participants belonged to lower socioeconomic status, followed by the middle (40.57%) and upper class (14%). It was observed that total cholesterol was significantly associated with blood sugar (p=0.0008), blood pressure (p=0.001), and body mass index (BMI) (p=0.018). There was no significant association among the risk factors of CHD such as smoking and alcohol with total cholesterol. Low-density lipoprotein level was significantly associated with BMI (p=0.0001) and blood sugar (p=0.003). There was a significant association among the risk factors for CHD such as smoking (p=0.002), alcohol, (p=0.017) blood sugar (p=0.004), and BMI (p=0.014) with triglyceride level. Conclusion: It was concluded from this study that various risk factors for CHD were associated with lipid abnormalities. Hence, a community-based education in this regard is of paramount importance.